A Laboratory Investigation on Flow Rate Coefficient for Compound Weir - Othman, Nur Aina Atirah; Md Ali, Zarina; Ahmad, Noor Aliza (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Abstract: The determination of the flowrate in an open channel can be obtained indirectly through the application of the weir. Therefore, the flow rate coefficient is significant as the value will differ based on the shape of the weir. Compound weirs are suitable shapes for rivers that have low flow levels during the dry season and high flow during the rainy season. The purpose of the study is to determine the flowrate coefficient, Cd values, using a rectangular-triangular weir. The method used was an experimental study by using nine models of compound weirs with different measurements of V-notch angle, ?, and length of weir, L. The highest value for Cd is 0.47 which characteristics weir, L = 0.10 m, ? = 50o (Model 2) at H = 0.076 m. Meanwhile, the lowest value of Cd is 0.11 which characteristics weir, L = 0.15 m, ? = 50o (Model 8) at H = 0.025 m. Furthermore, V-notch angle, ? = 50o is the best angle of V-notch when combined with all constant L (0.1 m, 0.12 m, and 0.15 m). The correlation between Cd and H, and Qexp and Qtheory show good relations between variables except for Model 7. It is shown that the flowrate and measurement of the weir influence the flowrate coefficient, Cd. In conclusion the value of the flow rate coefficient, Cd can be identified for high and low water flows before being used at the actual site. Therefore, an exact value of discharge is a design criterion that must be met by the hydraulic structure. If the discharge is overestimated, the structure might collapse, and if the discharge is underestimated, the structure might not last very long owing to weakness. Keywords: Compound weirs, Flowrate coefficient, experimental study, Rectangular-Triangular weir